Occupational Aspirations of Care Leavers and their Pathways to Work - Sabrina Göbel; Annabell Hansmeyer; Marei Lunz; Ulla Peters (Social Work & Society, 2021)
Young people leaving residential care (so-called care leavers) face various challenges during their transition. During the process of leaving care, they also deal with questions of their future occupation or profession and integration into the labour market. In this article, we present findings on care leavers' occupational aspirations and pathways into work based on qualitative longitudinal data and retrospective interviews with care leavers from Luxembourg. The analysis of the data points at the importance of care leavers having concrete career aspirations early on and pursuing realistic career goals. Without having occupational aspirations, they are more likely to drift, which also disorientates their transition out of residential care. The contrast of longitudinal data with the retrospective interviews shows that a meaningful connection of care and professional biography positively influences the pathways to work. Based on the results presented, implications for further research and social work with care leavers will be discussed.